Effect of Arenga pinnata Palm Wine on Surface Roughness of Acrylic and Thermoplastic Nylon: SEM Study - Tri Purnami Dewi; Dewi Farida Nurlitasari; Ni Putu Dita Kristiana Putri (Interdental Jurnal Kedokteran Gigi (IJKG), 2026)
Introduction: Surface roughness is an important property of denture base materials because it affects hygiene, comfort, and durability. Rough surfaces can retain debris and microorganisms, increasing the risk of halitosis and mucosal irritation. Tuak aren (Arenga pinnata palm wine), a traditional fermented beverage, contains alcohol and has an acidic pH that may alter denture base materials. This study evaluated the effect of tuak aren on the surface roughness of acrylic and thermoplastic nylon denture bases. Materials and Methods: Four groups were studied: acrylic plates (A1) and thermoplastic nylon plates (A2) immersed in distilled water as controls, and acrylic plates (B1) and thermoplastic nylon plates (B2) immersed in tuak aren as treatments. After 11 days of immersion, surface morphology was examined using scanning electron microscopy (SEM), and surface roughness was measured using a profilometer. Results: Descriptive analysis showed that A1 had the lowest surface roughness, while B2 had the highest. One-way ANOVA demonstrated significant differences among groups. LSD post hoc analysis revealed significant differences between B2 and groups A1, A2, and B1. SEM observations at 500× magnification showed microscopic surface changes after immersion in tuak aren. Profilometer measurements were consistent with SEM findings. Conclusion: Exposure to tuak aren increased the surface roughness of denture base materials, with the greatest effect observed in thermoplastic nylon plates.